APPLICATION OF THE ORDINARY LEAST SQUARE (OLS) METHOD IN THE ANALYSIS OF ECONOMIC GROWTH FACTORS DURING THE NEW NORMAL OF COVID-19 IN PADANGSIDIMPUAN CITY - Lilis Saryani (SEAN Institute, 2022)
The Government of the Republic of Indonesia has now entered a new normal phase of COVID-19 which has been running for almost two years where the Covid-19 pandemic period is still ongoing even though it has begun to decline starting in 2021 yesterday. However, this new normal is still unable to restore the existing situation as it was before the pandemic, one of which is the economic sector of the Indonesian people. The economic sector has had a very bad impact during the Covid-19 pandemic, because all previous economic activities of the community are still moving with conventional systems. This is deeply felt by business actors in traditional markets. The problem that occurs is that business actors are unable to rise quickly and are unable to compete with other business actors who are better prepared to make sales during the pandemic. The purpose of this study is to learn about the analysis of economic growth factors during the new normal period of the Covid-19 pandemic in Padangsidimpuan City by applying the Ordinary Least Square (OLS) method by utilizing technology as a promotion / marketing of products sold by business actors in the Sangkumpal bonang market in Padangsidimpuan city. The analysis method used in this study is a quantitative method using panel data using A Fixed Effect Model, the steps of this study are the collection of secondary data obtained from the Central Statistics Agency of the Agency after data analysis. Based on the results of the analysis obtained from the results of the study: partially using the Fixed Effect Model Analysis tool, it produces negative variables on the Human Development Index in Padangsidimpuan City, comparing the Economy related to the Economic Growth Index of the community in Padangsidimpuan City.